2013
DOI: 10.3390/antib2020236
|View full text |Cite
|
Sign up to set email alerts
|

Ricin and Ricin-Containing Immunotoxins: Insights into Intracellular Transport and Mechanism of action in Vitro

Abstract: Ricin is a type II ribosome inactivating protein (RIP) isolated from castor beans. Its high toxicity classifies it as a possible biological weapon. On the other hand, ricin linked to specific monoclonal antibodies or used in other conjugates has powerful medical applications. Ricin consists of an A-chain (RTA) that damages ribosomes and inhibits protein synthesis, and a B-chain that plays a role in binding and cellular uptake. A number of recent studies have demonstrated that ricin-induced inhibition of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 196 publications
(246 reference statements)
1
24
0
1
Order By: Relevance
“…This system has shown promising results in vivo, thus providing direct proof that ELRs can be linked to aptamers for use in breast cancer suicide gene therapy. Most previous studies with ricin have been performed in immunotherapy with RTA or the holotoxin and blocking of the galactose binding sites [40]. To the best of our knowledge, this is the first time that the whole ricin gene has been transferred into target cells as part of suicide gene therapy in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This system has shown promising results in vivo, thus providing direct proof that ELRs can be linked to aptamers for use in breast cancer suicide gene therapy. Most previous studies with ricin have been performed in immunotherapy with RTA or the holotoxin and blocking of the galactose binding sites [40]. To the best of our knowledge, this is the first time that the whole ricin gene has been transferred into target cells as part of suicide gene therapy in breast cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Ricin-induced apoptosis mediated by different caspases, depending on the cell type, has been also described in in vitro studies [37][38][39]. Most of the research into ricin has been performed in cancer immunotherapy using chain A or blocking the galactose-binding sites from chain B [40]. The results showed the ability of these immunotoxins to kill human myeloma, lymphoma and lung cancer cells, amongst others [41][42][43][44].…”
Section: Breast Cancer Is the Most Commonly Occurring Cancer Diagnosementioning
confidence: 99%
“…Due to its high toxicity, ricin is considered as a biological weapon. On the other hand, detailed knowledge of the ricin intercellular transport mechanisms raises the possibility of using it in medicine as a component of modern immunotoxins and vaccines (Słomińska-Wojewódzka & Sandvig, 2013). The previous study reported that EDEM1 and EDEM2 are involved in ricin transport out of the ER (Sokołowska et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Cellular resistance is due to defect in delivery of toxin to the cytosol [37][38][39][40] and organismal resistance is because of failure to form ADPr EF2 41 or poor starting of apoptosis. Resistance to apoptosis is a major obstacle to effective cytotoxic cancer therapy.…”
Section: Toxin Resistancementioning
confidence: 99%